CERN@School: Forming Nationwide Collaborations for Physics Research in Schools. (2nd January 2016) - Whyntie, T.
Abstract : CERN@school is a program that brings CERN, the European Organisation for Nuclear Research, into the classroom. By supplying schools with cutting-edge detector technology and giving them access to the Worldwide LHC Computing Grid, students in the United Kingdom are being offered the opportunity to conduct authentic research in the field of nuclear and particle physics. Thanks to the support of the Science and Technology and Facilities Council (STFC), the Royal Commission for the Exhibition of 1851, and the Institute of Physics, the program has resulted in a nationwide network of student scientists working together to conduct a number of research projects. This article looks at how CERN@school has achieved this, some of the ongoing experiments, and the potential for rolling out the approach across the world.